Β‐Catenin regulation of farnesoid X receptor signaling and bile acid metabolism during murine cholestasis. Issue 3 (26th January 2018) - Thompson, Michael D.; Moghe, Akshata; Cornuet, Pamela; Marino, Rebecca; Tian, Jianmin; Wang, Pengcheng; Ma, Xiaochao; Abrams, Marc; Locker, Joseph; Monga, Satdarshan P.; Nejak‐Bowen, Kari
Abstract : Cholestatic liver diseases result from impaired bile flow and are characterized by inflammation, atypical ductular proliferation, and fibrosis. The Wnt/β‐catenin pathway plays a role in bile duct development, yet its role in cholestatic injury remains indeterminate. Liver‐specific β‐catenin knockout mice and wild‐type littermates were subjected to cholestatic injury through bile duct ligation or short‐term exposure to 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine diet. Intriguingly, knockout mice exhibit a dramatic protection from liver injury, fibrosis, and atypical ductular proliferation, which coincides with significantly decreased total hepatic bile acids (BAs). This led to the discovery of a role for β‐catenin in regulating BA synthesis and transport through regulation of farnesoid X receptor (FXR) activation. We show that β‐catenin functions as both an inhibitor of nuclear translocation and a nuclear corepressor through formation of a physical complex with FXR. Loss of β‐catenin expedited FXR nuclear localization and FXR/retinoic X receptor alpha association, culminating in small heterodimer protein promoter occupancy and activation in response to BA or FXR agonist. Conversely, accumulation of β‐catenin sequesters FXR, thus inhibiting its activation. Finally, exogenous suppression of β‐catenin expression during cholestatic injury reduces β‐catenin/FXR complex activation of FXR to decrease total BA and alleviate hepatic injury. Conclusion: We have identified an FXR/β‐catenin interaction whose modulation through β‐catenin suppression promotes FXR activation and decreases hepatic BAs, which may provide unique therapeutic opportunities in cholestatic liver diseases. (Hepatology 2018;67:955–971)